Novel anticoagulants and laboratory testing. Issue 3 (17th April 2013) - Eby, C.
Summary The introduction of several oral direct anticoagulants within the past 2–3 years has dramatically changed clinical practice and has also impacted on utilization and interpretation of coagulation laboratory testing. This article reviews the effects of the oral thrombin inhibitor, dabigatran, and the oral factor Xa inhibitors, rivaroxaban and apixaban, on screening and diagnostic coagulation tests, and describes methods for measuring the their anticoagulant activity in plasma. Currently, there are evidence gaps regarding the role of laboratory testing for surveillance and management of adverse events associated with these new anticoagulants which do not require routine therapeutic drug monitoring. This is a rapidly changing field, and coagulation laboratory experts have a major role in ensuring patients receive appropriate testing and accurate interpretations of results.